The Belief of Guidance from God: A Case Study of Spiritual Well-Being Among Salafi's Students in Yogyakarta - Sriwiyanti, Sriwiyanti; Suseno, Miftahun Ni’mah; Saefudin, Wahyu (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2022)
The Salafi students who are literalists in understanding religion raise pros and cons such as preliminary results, even radical and extremist. This study aims to analyze the dynamics of the spiritual welfare of Salafis female students under prejudice and academic demands. The research is a case study qualitative approach, with an in-depth interview as a data collecting technique. The participants are three students aged 19-25 years, using attributes highlighting their identities, such as dark-colored robes and face-veils. The results showed that the participants' spiritual well-being varied. The personal, environmental, and transcendental domains have a positive description. However, the communal domain shows that two participants have problems building relationships with the environment and society. Reversely, one participant was able to make adjustments. Subsequently, there is one concept that stands out the most about Salafi students, the belief in guidance from God. It refers to a religious experience. Hence, the implications of this research, in the participant community, general students, and stakeholders, can comprehensively evaluate and enhance spiritual well-being among students.